Knowledge, attitude, and practice toward delirium and subtype assessment among Chinese clinical nurses and determinant factors: A multicentre cross-section study - Zhou, Wen; Zheng, Qiulan; Huang, Miao; Zhang, Chuanlai; Zhang, Huan; Yang, Li; Wu, Taiqin; Gan, Xiuni (Frontiers in Psychiatry, 2023)
Background Delirium, a confused transient state of consciousness, can be divided into hyperactive, hypoactive, mixed, and no motor subtypes, according to different clinical manifestations. Several studies have investigated delirium subtypes in the knowledge dimension, but few studies have investigated delirium subtype in the attitude and practice dimensions. The barriers, knowledge sources, and practice details regarding subtype assessment are unclear. Objectives This study had three objectives. First, we planned to investigate the KAP status regarding delirium and subtypes for nurses. Second, we wanted to identify factors affecting clinical nurses' KAP scores. Third, this study expected to explore more details regarding delirium and subtypes assessment, including assessment barriers, assessment instruments, and knowledge sources. Methods This multicentre cross-section study was conducted in 10 tertiary hospitals in three provinces, China, from January to April 2022. We investigated 477 nurses from six departments with a high prevalence. The self-developed KAP questionnaire regarding delirium and subtypes assessment had four parts: knowledge, attitude, practice, and source. Its reliability and validity were verified effectively by 2-round Delphi expert consultation. Results A total of 477 nurses from the general intensive care unit (ICU), specialty ICU, orthopedics, thoracic surgery, operating room, and geriatrics were 28.3, 22.4, 22.2, 10.5, and 5.2%, respectively. The total KAP score regarding delirium and subtypes assessment was 60.01 ± 6.98, and the scoring rate was 73.18%. The scoring rate for knowledge, attitude, and practice was 58.55, 83.94, and 51.70%, respectively. More than half (54.1%) were unaware of the delirium subtypes assessment instruments. A total of 451 (94.6%) participants recognized the importance of nursing work for delirium prevention. A total of 250 (52.4%) nurses occasionally or sometimes assessed delirium subtypes, and 143 (30.0%) never assessed for delirium subtypes. We found that age, department, technical title, familiarity with delirium, familiarity with delirium subtypes, delirium training, and subtype training affected the total KAP scores. ICU nurses achieved the highest scores. Conclusion Chinese nurses' KAP status regarding delirium and subtypes assessment were barely acceptable, and the attitude score was positive, but knowledge and practice needed improvement. Meanwhile, the department was one of the significant KAP factors, and ICU nurses did better in delirium and subtype assessment in knowledge and practice dimension than other departments. Systematic and scientific training processes including subtype content and assessment tools are required. Experience still drives nurses' assessments of delirium and subtype. Adding the delirium assessment into routine tasks should be considered.